Development of the Arabic family relation test among school students - Marwa Nasser Alrajhi; Kamisah Osman; Hussain Ali Alkharusi (Institute of Advanced Engineering and Science, 2026)
Family relationships are highly valued; therefore, their assessment is essential. Documented literature has emphasized the significance of family relationships in students’ different outcomes. However, there is a lack of psychometrically robust measures of family relationships in Arabic-speaking environments. This study aimed to develop the Arabic family relation test (AFRT) and examine its psychometric properties. The test explores six main dimensions of parent-child relationships: restrictiveness, affection, vulnerability, justice, acknowledgment, and trust. The cross-sectional quantitative design was utilized. The study sample included 601 school students (47.6% males) from grades 5, 7, 9, and 11, selected through a cluster-random sampling approach. The findings revealed a valid 60-item AFRT with a two-second-order-factor, six-first-order-factor factorial structure. Measurement invariance of the AFRT was achieved in the father-child model across groups of age and gender. However, measurement invariance was only supported across age groups in the mother-child model. The AFRT demonstrated good reliability, as indicated by Cronbach’s alpha, test-retest, split-half, and composite reliability. The researchers concluded that the AFRT is an appropriate tool for family assessment; however, further psychometric investigation is recommended. In addition, recommendations for implications and suggestions for future research were provided.